THE SIMULATION OF GRANULAR PARTICLE ON DRY AND MOISTURIZED POROUS HORIZONTAL SURFACES - Dewi Muliyati; Dadan Sumardani; Fauzi Bakri; Handjoko Permana; Erfan Handoko; Ni Larasati Kartika Sari (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
Simulations were carried out to visualize the ratio of granular attachment to porous surfaces. This simulation uses a uFlex three-dimensional simulation using three sizes of porous surface systems in the condition of the smallest human pores and the most extensive human pores and the condition of wet skin and dry skin. Each system was tested using five granular particle sizes according to the range of the makeup granules’ size to determine the optimal adhesive. The results show that the number of cosmetic granular particles entering the porous surface system is directly proportional to the porous surface volume and moisture and inversely proportional to the granular cosmetic size. The larger the cosmetic granular used, the less granular enters the pore.